Judicial Justice and the European Regulation on Artificial Intelligence - Ayuda, Fernando Galindo (Frontiers in Law, 2024)
The study has identified several difficulties in effectively implementing artificial inteligence (AI) techniques in judicial proceedings. The approval of regulations, such as Spain's Royal Decree-Law 6/2023, is insufficient for Judges and legal professionals to use these technologies effectively. Several reasons for these challenges are highlighted. Firstly, judicial proceedings and the resulting sentences must be approved by all participants, including the parties involved, Lawyers, Prosecutors, and Judges. The focus should be on the specific conflict and relevant legal texts or precedents, not on AI-generated models based on past data, which may be biased.Secondly, AI technologies are not designed to assist in the specific tasks required by Judges and other officials responsible for processing judicial proceedings. Judicial processes are governed by strict constitutional, procedural, and substantive norms that AI systems are not equipped to handle without significant human oversight.The study also references critical experiences in other countries and opinions from the General Council of the Judiciary in Spain, which point out the lack of precision in the Spanish regulation regarding the use of AI in judicial activities. This indicates that the existing legal framework has not adequately considered the complexities of integrating information and communication technologies into judicial processes. Therefore, promoting AI technologies in judicial applications requires not only regulatory approval but also comprehensive reforms to existing norms and the creation of precise complementary regulations. These measures must align with the legal system and, especially, with the AI Regulation approved by the European Parliament and Council.